2023
DOI: 10.1021/acs.inorgchem.3c00055
|View full text |Cite
|
Sign up to set email alerts
|

Structural Regulation of Two Polyoxometalate-Based Metal–Organic Frameworks for the Heterogeneous Catalysis of Quinazolinones

Abstract: Two dimeric {ε-Zn 4 PMo 12 }-based metal−organic frameworks (MOFs), [ε-PMo 8 V Mo 4 VI O 34 (OH) 6 Zn 4 ][LO] (SDUT-21, LO = [5-((4′-carboxybenzyl)oxy)isophthalic acid]) and [TBA] 3 [ε-PMo 8 V Mo 4 VI O 37 (OH) 3 Zn 4 ][LN] (SDUT-22, TBA + = tetrabutylammonium ion, LN = [5-((4-carboxybenzyl)imino)isophthalic acid]), combining the advantages of polyoxometalates (POMs) and MOFs, were synthesized by the one-pot assembly strategy. The dimeric {ε-Zn 4 PMo 12 } units act as nodes that are linked by the flexible liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…36,37 We have been committed to the fabrication of MOFs with novel fluorescence sensing ability and/or catalytic functions. [38][39][40][41][42][43][44][45][46][47][48] In this work, two isostructural penetrating Zn/Co-MOFs, namely {[Zn(HL)(bpea)]•DMF} n (Zn-MOF-1) and {[Co(HL)(bpea)]•DMF} n (Co-MOF-2), were assembled from an ether-containing carboxylic acid of 3-(3,5-dicarboxybenzyloxy)benzoic acid (H 3 L). Both MOFs had multifunctional fluorescence sensing and catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 We have been committed to the fabrication of MOFs with novel fluorescence sensing ability and/or catalytic functions. [38][39][40][41][42][43][44][45][46][47][48] In this work, two isostructural penetrating Zn/Co-MOFs, namely {[Zn(HL)(bpea)]•DMF} n (Zn-MOF-1) and {[Co(HL)(bpea)]•DMF} n (Co-MOF-2), were assembled from an ether-containing carboxylic acid of 3-(3,5-dicarboxybenzyloxy)benzoic acid (H 3 L). Both MOFs had multifunctional fluorescence sensing and catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The study of MOFs has been rapidly developed in the past decades due to not only the fascinating crystallography of MOFs but also the potential applications in various fields including adsorption and separation, catalyst, and so on. Due to the advantages of adjustable channels, adjustable pore size, large specific surface area, low density, and good chemical stability, MOFs have been widely used as recyclable heterogeneous catalysts in various organic reactions. Usually, when MOFs are used in catalysis, the active site of the catalysts are the metal centers of the MOFs, which can activate the substrates and lower the reaction energy barrier to allow the reaction to proceed smoothly. Therefore, the selection of suitable metal ions is very important for the construction of MOF catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…It is very conducive to the interaction of guest molecules with oxygen-rich groups. Several previous studies have reported on porous materials that effectively capture less acidic carbon dioxide molecules or other saccharide molecules by the obvious hydrogen bonding interactions of the introduced multiamide groups. However, a slight change in the configuration of active sites of the host or guest molecules might change the interactions and binding abilities between them and thus also affect the stability or the selectivity of the binding guests . As a consequence, accurate matching is highly required to construct a stable supramolecular system.…”
Section: Introductionmentioning
confidence: 99%
“…20−24 However, a slight change in the configuration of active sites of the host or guest molecules might change the interactions and binding abilities between them and thus also affect the stability or the selectivity of the binding guests. 25 consequence, accurate matching is highly required to construct a stable supramolecular system. Herein, by incorporating Co(II) ions as construction nodes and a flexible ligand TAP containing three functional amides and one secondary amino group as guest-interacting sites, we report an MOC (Co-TAP) with a pseudotetrahedral structure; the introduction of additional secondary amino groups in Co-TAP exhibits a strong selective recognition of uridine over other RNA nucleosides with similar size and structures via a fluorescent response.…”
Section: Introductionmentioning
confidence: 99%